Early isolated subarachnoid hemorrhage versus hemorrhagic infarction in cerebral venous thrombosis - Kobal, Jan (Radiology and oncology (Ljubljana), 2022)
Background: Cerebral venous thrombosis (CVT) is a rare cerebral vascular disease, the presentation of which is highly variable clinically and radiologically. A recent study demonstrated that isolated subarachnoid hemorrhage (iSAH) in CVT is not as rare as thought previously and may have a good prognostic significance. Hemorrhagic venous infarction, however, is an indicator of an unfavorable outcome. We therefore hypothesized that patients who initially suffered iSAH would have a better clinical outcome than those who suffered hemorrhagic cerebral infarction. Patients and methods: We selected patients hospitalized due to CVT, who presented either with isolated SAH or cerebral hemorrhagic infarction at admission or during the following 24 hours: 23 (10 men) aged 22-73 years. The data were extracted from hospital admission records, our computer data system, and the hospital radiological database. Results: The iSAH group consisted of 8 (6 men) aged 49.3 ± 16.2 and the hemorrhagic infarction group included 15 (4 men) aged 47.9 ± 16.8. Despite having a significantly greater number of thrombosed venous sinuses/deep veins (Mann-Whitney Rank Sum Test, p = 0.002), the isolated SAH group had a significantly better outcome on its modified Rankin Score (mRs) than the hemorrhagic infarction group (Mann-Whitney Rank Sum Test, p = 0.026). Additional variables of significant impact were edema formation (p = 0.004) and sulcal obliteration (p = 0.014). Conclusions: The patients who suffer iSAH initially had a significantly better outcome prognosis than the hemorrhagic infarction patients, despite the greater number of thrombosed sinuses/veins in the iSAH group. A possible explanation might include patent superficial cerebral communicating veins.
Keywords: cerebral venous thrombosis; hemoragičen možganski infarkt; hemorrhagic brain infarction; možganska venska tromboza; subarachnoid hemorrhage; subarahnoidna krvavitev